Budaya Literasi di Pesantren: Analisis antara Tradisi, Modernitas, dan Tantangan Global - Syarif Bahaudin Mudore; Muh. Zacky Fadhil Rachmat (Yayasan Zia Salsabila, 2025)
This study aims to analyze the dynamics of pesantren literacy culture amid the intersection of classical Islamic scholarly traditions, educational modernity, and the demands of globalized information. As one of the oldest Islamic educational institutions in Indonesia with distinctive literacy traditions, pesantren are increasingly challenged by modernity and globalization, which are often perceived as forces capable of eroding their identity and epistemic continuity. This research employs a qualitative approach using library research methods, drawing on academic literature related to pesantren literacy culture. Data were analyzed using Bourdieu’s theory of habitus, Gee’s Critical Literacy Studies, and Giddens’s disembedding mechanisms to map the dialectical relationship between pesantren’s traditional structures and broader social transformations. The findings indicate that pesantren literacy culture remains deeply rooted in classical scholarly habitus, which maintains epistemic continuity and cultural capital, while modernization and globalization stimulate innovation through the integration of digital technology, the strengthening of critical literacy, and curriculum development. The interaction among these three dimensions produces a form of literacy that is adaptive, selective, and contextually grounded, demonstrating that the transformation of pesantren literacy is not a simple shift between tradition and modernity, but a complex and ongoing process of negotiation that preserves the institution’s distinctiveness.